Some Theorems in the Theory of Efficient Transfers - Olsen, Edgar O. (Journal of Political Economy, 1971)
This paper proves a positive theorem about the effects of any voluntary voucher scheme. It also describes a situation in which vouchers can result in optimal resource allocation and shows what the face values of and charges for the voucher must be in order to achieve optimality in this situation. The paper concludes with applications of the theorems to several proposed voucher schemes.